Arabic Loanwords in Kamus Dewan Perdana: Questions of Etymology, Word Class and Definition - Abu Bakar, Noorazlin; Zahid, Indirawati; Wan Ali, Wan Zailan Kamaruddin (Jurnal Arbitrer, 2024)
Kamus Dewan Perdana (KDP) is the largest and most complete dictionary of the Malay language (ML) and is the latest edition of the Dewan Bahasa dan Pustaka (DBP), which targets ML native speakers and non-native speakers who are proficient in using ML. This study aims to identify Arabic loanwords (AL) in KDP and analyse questions of their entry regarding the aspects of etymology, word class, and definition from the perspective of users and researchers by using Qualitative Comparative Analysis (QCA) as the methodology. The findings of this study found a total of 2847 entries of AL in KDP, which include 66% labelled Arabic (Ar) and 34% unlabelled. This study also found seven questions regarding AL entries in the KDP from the aspects of etymology, word class, and definition. Three questions arise from the etymological aspect, namely, (1) the inconsistent omission of etymological labelling, (2) the differences in terms of etymological labelling between KDP and Kamus Dewan Edisi Keempat (KDE4), and (3) justification for the source language information of the loanword placed at the end of the entry in the KDP; a question arises from the aspect of word class, which is the inconsistency in word class labelling for AL expression entries; and three questions from the aspect of definition, namely (1) the inaccuracy in the definition of homonymous word variations in KDP, (2) the absence of definition of the AL entries in the KDP and (3) the deletion of AL entry in the KDP. The results of this study serve as user feedback, which contributed to DBP as the body responsible for improving the compilation of KDP as well as other dictionaries such as Kamus Besar Bahasa Indonesia (KBBI), Cambridge Advanced Learner’s Dictionary (CALD), Longman Dictionary of Contemporary English New Edition (LDCENE), Oxford English Dictionaries (OED), and Concise Oxford English Dictionaries (COED). This improvement will in turn be able to provide complete vocabulary information to the user community, both among native speakers and non-native speakers.